What matters most : the Get Your Shit Together guide to wills, money, insurance, and life's "what-ifs" - Reynolds, Chanel (Harper Wave, 2019)
Founder of popular website Get Your Shit Together blends personal story and must-have advice in the ultimate guide to getting your affairs in order--from wills and advance directives to insurance, finances, and relationships--before the unthinkable happens.